1996
DOI: 10.1172/jci118830
|View full text |Cite
|
Sign up to set email alerts
|

Molecular basis of the human dihydropyrimidine dehydrogenase deficiency and 5-fluorouracil toxicity.

Abstract: Dihydropyrimidine dehydrogenase (DPD) deficiency constitutes an inborn error in pyrimidine metabolism associated with thymine-uraciluria in pediatric patients and an increased risk of toxicity in cancer patients receiving 5-fluorouracil (5-FU) treatment. The molecular basis for DPD deficiency in a British family having a cancer patient that exhibited grade IV toxicity 10 d after 5-FU treatment was analyzed. A 165-bp deletion spanning a complete exon of the DPYD gene was found in some members of the pedigree ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
174
4
12

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 325 publications
(196 citation statements)
references
References 24 publications
6
174
4
12
Order By: Relevance
“…As a result, 5-FU degradation generally occurs in all tissues, including tumour tissues, but it reaches its highest level in the liver (Ho et al, 1986). In fact, a congenital deficiency of DPD can result in severe life-threatening toxicity when 5-FU is administered (Wei et al, 1996). In contrast, many experimental studies have demonstrated the intratumoural DPD activity to affect the resistance to 5-FU (Beck et al, 1994;Ishikawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, 5-FU degradation generally occurs in all tissues, including tumour tissues, but it reaches its highest level in the liver (Ho et al, 1986). In fact, a congenital deficiency of DPD can result in severe life-threatening toxicity when 5-FU is administered (Wei et al, 1996). In contrast, many experimental studies have demonstrated the intratumoural DPD activity to affect the resistance to 5-FU (Beck et al, 1994;Ishikawa et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A set of studies [26][27][28][29][30] highlighted the pivotal role of DPYD gene polymorphisms in the insurgence of severe toxicity and led to the definition of pharmacogenetic guidelines for the diagnostic use of some DPYD SNPs testing (i.e., DPYDrs3918290, DPYD-rs67376798, and DPYD-rs55886062). 1 These results were further validated in successive studies which assessed the role of these SNPs in prospective clinical trials, 3,8,9 in retrospective patients collections 7,10,11 and in meta-analysis studies.…”
Section: Cancer Therapymentioning
confidence: 99%
“…The most common DPD mutation is located in the splice site of intron 14 (IVS14+1G>A), resulting in the deletion of exon 14 and thereby creating a nonfunctional enzyme [5,6]. It has been suggested that this mutation accounts for about 25 percent of 5-FU-associated toxicity [7].…”
Section: Introductionmentioning
confidence: 99%